Andiamo al museo! Un progetto interdisciplinare a Scienze della Formazione Primaria - Domenici, Valentina (Chimica nella Scuola, 2024)
In this contribution a didactic project by the University of Pisa for students attending the degree course in Primary Education is briefly described.